2017
DOI: 10.18632/oncotarget.22895
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Golgi apparatus to overcome acquired resistance of non-small cell lung cancer cells to EGFR tyrosine kinase inhibitors

Abstract: Epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (EGFR-TKIs) were demonstrated to provide survival benefit in patients with non-small cell lung cancer (NSCLC) harboring activating mutations of EGFR; however, emergence of acquired resistance to EGFR-TKIs has been shown to cause poor outcome. To overcome the TKI resistance, drugs with different mode of action are required. We previously reported that M-COPA (2-methylcoprophilinamide), a Golgi disruptor, suppressed the growth of gastric cancers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…A recent study has confirmed the importance of the Golgi apparatus in overcoming the acquired resistance of lung adenocarcinoma to EGFR tyrosine kinase inhibitors. Disrupting the Golgi apparatus via inhibition of ADP ribosylation factor 1 (ARF-1) exerts anti-tumor activity against EGFR-activated tumor cells [ 33 ]. Similarly, inhibition of GORASP2 might disrupt the membrane dynamics of the Golgi apparatus, thus leading to a substantial anti-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has confirmed the importance of the Golgi apparatus in overcoming the acquired resistance of lung adenocarcinoma to EGFR tyrosine kinase inhibitors. Disrupting the Golgi apparatus via inhibition of ADP ribosylation factor 1 (ARF-1) exerts anti-tumor activity against EGFR-activated tumor cells [ 33 ]. Similarly, inhibition of GORASP2 might disrupt the membrane dynamics of the Golgi apparatus, thus leading to a substantial anti-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic resistance is a stumbling block preventing the survival and worsening the quality of life of patients with PCa and other cancers. Numerous strategies have been attempted to overcome therapeutic resistance, including the classic approach of targeting multiple drug resistant genes responsible for drug transport and accumulation in cancer cells [60] , targeting mechanistically alternative signaling pathways [61] , or designing stronger antagonists bypassing the resistance mechanism [62] , identifying the recurrence-initiating stem cells in tumors and designing specific agents to target this resistance-related population [63] , and characterizing and modulating activated non-cancer cells in the tumor microenvironment including cancer associated fibroblasts, myeloid, immune and endothelial cells and mesenchymal stem cells in a broad-spectrum of cancer types to prevent their ability to confer therapeutic resistance [64] , [65] . Castration-resistant PCa (CRPC) and metastatic CRPC (mCRPC) are the lethal forms of PCa, often treated by androgen antagonists, abiraterone acetate, and enzalutamide or microtubular inhibitor taxanes [66] .…”
Section: Targeting Mitochondrial and Lysosomal Organelles To Overcomementioning
confidence: 99%
“…Notably, Arf1 has been reported to be activated downstream of the EGFR in triple negative breast cancer cells (TNBC) cells [43]. Since then, several reports have underlined the importance of the Arf1/EGFR axis in cancer cells progression [46][47][48]. In HNSCC, we have previously evidenced direct interaction between Arf1 and phospho-EGFR and highlighted the critical role of the EGFR-Arf1 complex in driving HNSCC progression [14].…”
Section: Discussionmentioning
confidence: 76%